Development and Implementation of a Uniform Dental School‐Wide Electronic Treatment Consenting Process for Patients. Issue 9 (1st September 2018) - Robinson, Fonda G.; Fields, Henry W.; Ness, Gregory M.; Heinlein, David J.; Gellin, Robert G.; Larsen, Peter E.
Abstract : One approach to enhancing quality care outcomes and patient safety is through effective implementation of clinical risk reduction strategies. Clinical risk identification at The Ohio State University College of Dentistry revealed lack of a standardized informed consenting process for patients. The purpose of this project was to develop and implement a uniform college‐wide informed consenting process. An operating procedure was also developed. The resulting consenting documents used a uniform approach in which clinics could use a basic readable and processable informed consent template. The template was edited for appropriate content suitable for an electronic health record. Implementing an operating procedure along with associated contemporary uniform electronic informed consent forms was realized through efforts of a core team with informed consenting experience. The core team developed the template and the majority of all documents before editing all division‐based consents. This method relied on growing expertise and momentum. Outcomes of chart audits following implementation of the new electronic informed consent forms showed a transitory increase in missing consent forms. Subsequently, the number of missing consent forms decreased to near pre‐implementation levels. Patient refunds related to missing informed consent issues dropped, and patient satisfaction remained high throughout the project. Other institutions can use this project as a guide for developing their own uniform consent forms and process.